ANALISIS KESULITAN SISWA DALAM MEMAHAMI MATERI MATA PELAJARAN GEOGRAFI SEMESTER GANJIL MENGENAI DINAMIKA PLANET BUMI SEBAGAI RUANG KEHIDUPAN (STUDI PADA SISWA KELAS X DI SMAN 1 PADANG) - diniah mukhlis; Syafri Anwar (JURNAL BUANA, 2020)
This research is motivated by the results of learning or daily tests of students who dropped dramatically in KD 3.4 concerning the dynamics of planet Earth as a space of life. This study aims to determine the factors that cause students' difficulties in understanding geography subject matter in odd semester about the dynamics of planet Earth as a space of life and the efforts made by students and teachers in overcoming it. This study uses a qualitative descriptive method. Research informants are teachers and class X students consisting of X MIA 1, X MIA 8 and X IIS whose learning outcomes in KD 3.4 are incomplete or under KKM. Difficulty in understanding the material because the material is too difficult so that makes students less able to digest, remember, and understand the material. While the factors that cause students difficulty in understanding subject matter are lack of interest in reading and not repeating lessons, teachers, subject matter, study habits, and the role of parents. Efforts made by students in overcoming difficulties understanding the subject matter are self-study by re-reading textbooks, browsing and searching on the internet, asking friends and teachers. While the efforts made by the teacher are repeating and reviewing material that is not yet understood by students conducting remedial to students whose grades are below KKM, and conducting evaluations.